On deferred statistical boundedness of order ? - Et, Mikail; Bhardwaj, Vinod K.; Gupta, Sandeep (Taylor & Francis Inc, 2022)
In this paper, we introduce and examine the concept of deferred statistical boundedness of order alpha and give the relation between statistical boundedness and deferred statistical boundedness of order alpha. Apart from studying the K_othe-Toeplitz duals of S-p, q(alpha) (b), the space of deferred statistically bounded sequences of order alpha, a decomposition theorem is also established. Finally we give a general description of inclusion between two deferred alpha-statistical methods of boundedness.
Keywords: Statistical boundedness; dual spaces; statistical convergence; Cesaro summability